Job search monitoring and unemployment duration in Hungary: evidence from a randomised control trial - John Micklewright; Gyula Nagy (Institute for the Study of Labor (IZA), 2005)
The impact of the administration of unemployment benefits on time spent unemployed is a neglected issue in discussion of incentive effects in Central and Eastern Europe. We use Labour Force Survey data, administrative registers and inspection of benefit office practices to show that there is good reason to investigate this issue in Hungary. We then report on results from a field experiment of the impact of tightening the administration of benefits in which benefit claimants were randomly assigned to treatment and control groups. Treatment has quite a large effect on durations on benefit of women aged 30 and over while we find no effect for younger women or for men.
Keywords: J64; J65; P23; 330; experiment; job search; unemployment insurance; Hungary; Arbeitslosenversicherung; Langzeitarbeitslosigkeit; Arbeitsuche; Wirkungsanalyse; Ungarn